Degumming of raw silk via steam treatment. (1st December 2018) - Wang, Rui; Zhu, Yaofeng; Shi, Zhuo; Jiang, Wenbin; Liu, Xiangdong; Ni, Qing-Qing
Abstract: A novel degumming approach by using steam treatment is proposed to minimize water pollution and consumption in silk wet processing. Sericin removal of Bombyx mori silk fibers was carried out with pressurized steam. The degumming ratio, fine structure and physical properties of the degummed silk fibers as well as energy efficiency were investigated to elucidate the degumming effects of steam treatment. Compared to the conventional neutral soap and sodium carbonate (Na2 CO3 ) degumming methods, sericin can be removed by steam treatment without any chemicals, and the degumming ratio as well as physicochemical properties of the degummed silk fibers maintained at a desirable level. Energy efficiency and cost analysis showed that steam degumming is more energy-efficient and economical than the conventional chemical degumming methods. Results showed that steam treatment is a feasible silk degumming method with the benefits of reduction in water pollution and energy consumption. Graphical abstract: Image 1 Highlights: Silk degumming was performed by using steam without any chemicals. Sericin can be effectively removed with steam treatment. The physicochemical properties of the degummed fibers were not changed essentially. Steam degumming has lower cost than the conventional degumming methods.